2014
DOI: 10.1093/icvts/ivu138
|View full text |Cite
|
Sign up to set email alerts
|

Sub-xyphoid pleural drain as a determinant of functional capacity and clinical results after off-pump coronary artery bypass surgery: a randomized clinical trial

Abstract: Sub-xyphoid pleural drain determined better functional capacity and exercise tolerance with a smaller pulmonary shunt fraction and improved clinical outcomes compared with intercostal pleural drainage after off-pump coronary artery bypass surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 27 publications
2
16
0
3
Order By: Relevance
“…However, cerebral injury following resuscitation remains difficult issue for complete rehabilitation (21). Following successful CPR, the autonomic circulation recovery of the cerebral blood flow causes cerebral-reperfusion injury and may cause further aggravation of the prognosis of cerebral functions and mortality (22). In present study, quercetin significantly reduced the LVDs, increased the EF, FS, SV and CO, and enhanced left ventricle weight/body weight in CPR model rats.…”
Section: Discussionsupporting
confidence: 48%
“…However, cerebral injury following resuscitation remains difficult issue for complete rehabilitation (21). Following successful CPR, the autonomic circulation recovery of the cerebral blood flow causes cerebral-reperfusion injury and may cause further aggravation of the prognosis of cerebral functions and mortality (22). In present study, quercetin significantly reduced the LVDs, increased the EF, FS, SV and CO, and enhanced left ventricle weight/body weight in CPR model rats.…”
Section: Discussionsupporting
confidence: 48%
“…According to previous research, due to the multifactorial impairment of pulmonary function [5,19-23] , there is a significant risk of respiratory complications during the postoperative period, which may result in prolonged time of mechanical ventilation, longer postoperative hospital stay, and possibly death [5,20,21] . Those results are in agreement with our findings; the CMV and L-OLS groups with greater pulmonary function impairment also showed a significantly greater intubation time and hospital stay in comparison to the E-OLS group.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory events were also evaluated (atelectasis, pleural effusions, and pneumonia). Pleural effusion was considered relevant when exceeding the phreno-costal angle and fluid drainage was monitored hourly [ 4 ] . Atelectasis was acknowledged when a clear atelectasis radiological shadow exceeded 15 mm in width [ 4 ] ; linear atelectasis was disregarded in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated blood lactate level and low central venous oxygen saturation (ScvO 2 ) have been independently associated with an increased risk of complications and longer postoperative hospital stay following cardiac surgery, contributing to increased morbidity and mortality after coronary artery bypass surgery (CABG) [ 1 - 3 ] . In addition, several studies have shown that postoperative pulmonary dysfunction following CABG is inevitable, which could increase the occurrence of respiratory complications and delay recovery [ 4 - 6 ] .…”
Section: Introductionmentioning
confidence: 99%